2020
DOI: 10.35580/sainsmat92153842020
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kandungan Oksida Logam Zeolit Alam Sulawesi Selatan Teraktivasi Asam Klorida

Abstract: Penelitian ini bertujuan untuk mengetahui kandungan oksida logam pada zeolit alam sebelum di aktivasi dan setelah diaktivasi. Aktivator yang digunakan adalah asam klorida 6 M. Analisis kandungan oksida logam dilakukan menggunakan instrument X-Ray Fluoresence (XRF). Hasil yang diperoleh menunjukkan, terjadinya penurunan kadar pengotor setelah zeolit teraktivasi asam. Kandungan Al2O3; SiO2; K2O dan CaO sebelum aktivasi berturut-turut adalah 2.15%; 86.34%; 4.32%; dan 2.54% adapun setelah aktivasi berturut-turut a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
0
4
0
1
Order By: Relevance
“…Beberapa penelitian terkait pemanfaatan zeolit alam lebih dikhususkan pada peningkatan efektivitas dan efisiensi proses industri dan pencemaran lingkungan (Putri dan Sabani, 2018;Setiawan dkk., 2018;Putri dan Side, 2020;Wijaya dkk., 2021). Pratomo dkk., (2017) melaporkan pemanfaatan zeolit alam teraktivasi asam fosfat (H 3 PO 4 ) sebagai adsorben ion Logam Cd (II) dalam laruta.…”
Section: Pendahuluanunclassified
“…Beberapa penelitian terkait pemanfaatan zeolit alam lebih dikhususkan pada peningkatan efektivitas dan efisiensi proses industri dan pencemaran lingkungan (Putri dan Sabani, 2018;Setiawan dkk., 2018;Putri dan Side, 2020;Wijaya dkk., 2021). Pratomo dkk., (2017) melaporkan pemanfaatan zeolit alam teraktivasi asam fosfat (H 3 PO 4 ) sebagai adsorben ion Logam Cd (II) dalam laruta.…”
Section: Pendahuluanunclassified
“…Adsorption occurs by the attractive force between the adsorbed molecule (adsorbate) and the adsorbing material (adsorbent). A molecule can be adsorbed if the adhesion force between the adsorbate molecule and the adsorbent molecule is greater than the cohesion force in each molecule [10].…”
Section: 3mentioning
confidence: 99%
“…The large surface is formed due to the presence of fine pores in the solid. In addition to surface area and pore diameter, distribution density and particle size are the most important characteristics of an adsorbent [10].…”
Section: 3mentioning
confidence: 99%
“…Thus, based on the mineral constituent compounds, the Gowa district natural clay sample has a fairly high alumina silica content. In addition, Putri and Pratiwi (2017) also reported that natural clay from South Sulawesi has a high content of silica (65.39%) and alumina (9.02%) as well as some impurities contained therein such as Fe2O3 and TiO2. The high content of impurities in natural clay from South Sulawesi can affect the characteristics and durability of the material produced using clay as a raw material.…”
Section: Introductionmentioning
confidence: 95%
“…In Indonesia the utilization of clay is only for the manufacture of furniture and ceramics. The application of natural clay such as raw material for ceramic, adsorbent, and catalyst support (Putri et al 2018;Putri and Pratiwi 2016;Putri et al 2022). Even though the clay content in Indonesia which is spread across several provinces contains alumina silica which can be utilized in various sectors.…”
Section: Introductionmentioning
confidence: 99%